Review Article The most common complication of Acute intermittent porphyria and its occurrence - Kudhair, Ahmed Hassan; Abdalruda, Khalid Hassan; Abbas, Hanan Diekan; Fakhrildin, Muhammad-Baqir M-R. (Eximia, 2022)
Porphyria is one of the most common complications related to Heam metabolism, although the incidence of this disease is very rare but due to it is unlimited complications this push the thought to word the concentration about the type of each complication and its type of the disease. Treatment of this disease is not the same as what it was in the past due to that the development of the treatment protocol and the development of genemapping make the incidence of this disease is very rare but still the disease is one of the most important health problems that it occur Method: a study was conducted to follow the most common complication of the type of porphyria and its occurrence in each type of this disease Results : data showed that the most common complication of the acute intermittent porphyria (AIP)is the neurological complications although some researches indicated an occurrence of the abdominal pain, constipation and even intestinal narcosis.